The Dry Plant Extract of Common Bean Seed (Phaseoli Vulgari Pericarpium) does not Have an Affect on Postprandial Glycemia in Healthy Human Subject - Aleksandra Cerović; Ivanka Miletić; Aleksandra Konić-Ristić; Ivana Baralić; Brižita Djordjević; Ivana Djuričić; Miodrag Radusinović (Biomolecules & Biomedicine, 2006)
The aim of present study was to assess the effects and safety of a dry Phaseoli vulgari pericarpium (PVP) extract on postprandial glycemia in healthy participants. A randomized crossover experiment where participants received either PVP extract or placebo. Chemical compounds in dry extract were assessed by established methods. Eighteen healthy participants (9 male and 9 female) aged 29+/-4,8 years, body mass index (BMI) 23+/-3,7 kg/m(2) were recruited among students and staff at the Faculty of Pharmacy, University of Belgrade. All participants were able to follow the study protocol without difficulty. The participants received either PVP extract or placebo 30 minutes before a 50g oral glucose tolerance test (OGTT). The protocol followed the guidelines for the OGTT with blood samples drawn at 0, 15, 30, 60, 90 and 120 min. This study demonstrated that there was no significantly effect of the PVP extract on incremental blood glucose (IBG) and their areas under the curve (AUC) neither male nor female participants. However, IBG together with AUC changes were significantly lower in male compared with female participants in treated and untreated groups. The presence of chrome, soluble fiber, vitamin C, protein, glucose and lectins were also quantified. The applied amount of PVP extract was unable to produce the postprandial hypoglycemia. We assumed that amounts of chrome, soluble fiber, vitamin C which have beneficial effects on diabetes treatment were sufficient to produce hypoglycemia.